Developing a tool to support diagnostic delivery of dementia - Bennett, Claire (2018)
Current political drivers are set to increase the volume of people receiving a dementia diagnosis. However, there are problems with how diagnoses are being delivered, with people reporting it to be confusing, anxiety provoking, and being generally dissatisfied. Limited guidance exists that could help improve the delivery and steps are required to address this. Research has begun to explore the components of a good delivery of a diagnosis of dementia, however interventions to support clinicians to deliver diagnoses are limited. This project’s overarching aim was to develop a prototype tool that has future potential to be used by clinicians, patients, and companions who are involved in the delivery of diagnoses of dementia.